KATA KASAR DALAM BAHASA BALI: SUATU TINJAUAN TEORI RELEVANSI - Mahardika, I Putu Permana; Fitriana, Ita (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
A harsh word is a term that is considered insulting or demeaning to a participant in communication. This paper examines the use of harsh words in the Balinese based on relevance theory. In Balinese, harsh words are not only interpreted literally but also non-literally, depending on the context. The data in this article were collected through observation. The analysis results indicate that although harsh words tend to have harsh or negative connotations, they are often used to create relevance in communication so that the participant can easily infer meaning based on the context of the utterance. Thus, harsh words are not merely expressions of impoliteness but also serve as effective communication.